Development of Flipbook Learning Media to Increase Students' Interest in Learning the Material Lines and Angles at SMPN 9 Pontianak - Nurhayati, Nurhayati; Yani T, Ahmad; Siregar, Nurfadilah (JPMI (Jurnal Pendidikan Matematika Indonesia), 2025)
The low interest of students in learning mathematics makes teachers have to innovate in developing a media that can motivate students in participating in mathematics learning. This study aims to develop flipbook learning media to increase students' interest in learning the material of lines and angles with the criteria of feasible, practical, and effective. The research method used is the Research and Development method which refers to the 4-D model which is modified only to the Develop stage, namely Define, Design, Develop, and Desseminate. The subjects of the study were students of class VIIB of SMP Negeri 9 Pontianak. The results of the study obtained were the results of media expert validation of 82.96% and material expert 90.62% with the category of feasible to use. The results of the student response rate were 80.21% and teachers 92.65% with the category of practical to use. While the results of the t-test showed that there was a significant difference in student learning outcomes before and after the application of flipbook learning media, this indicates that flipbook learning media is effective to use. Pengembangan Media Pembelajaran Flipbook Untuk Meningkatkan Minat Belajar Siswa Pada Materi Garis Dan Sudut Di SMPN 9 PontianakABSTRAKRendahnya minat siswa dalam belajar matematika membuat guru harus melakukan inovasi dalam mengembangkan suatu media yang dapat membuat siswa termotivasi dalam mengikuti pembelajaran matematika. Penelitian ini bertujuan untuk mengembangkan media pembelajaran flipbook untuk meningkatkan minat belajar siswa pada Materi garis dan sudut dengan kriteria layak, praktis, efektif. Metode Penelitian yang digunakan ialah metode Penelitian dan pengembangan yang mengacu pada model 4-D yang dimodifikasi hanya sampai tahao Develop yaitu Define, Design, Develop, dan Desseminate. Subjek penelitian ialah siswa kelas VIIB SMP Negeri 9 Pontianak. Hasil penelitian yang di peroleh yaitu hasil valiasi ahli media 82,96% dan ahli materi 90,62% dengan kategori layak digunakan. Hasil angkat respon siswa 80,21% dan guru 92,65% dengan kategori praktis digunakan. Sedangkan hasil uji-t menunjukkan bahwa adanya perbedaan yang signifikan pada hasil belajar siswa sebelum dan sesudah penerapan media pembelajaran flipbook, hal ini menunjukkan bahwa media pembelajaran flipbook efektif digunakan.Kata Kunci : Flipbook; Garis; Sudut; Define; Design; Develop; Desseminate 4-D.